The Pendampingan Pengembangan Eco-Canteen di SMAN 1 Padalarang Sebagai Strategi Menuju Sekolah Sehat dan Berkelanjutan - Putri, Tika Novis; Sujana, Octavia Maryanche; Hastika, Nunung; Azizah, Dira Nur; Dewi, Nova Puspa (Jurnal Pengabdian Tri Bhakti, 2024)
A healthy and sustainable school canteen is an important step in supporting the healthy school movement. SMAN 1 Padalarang has the same mission to create a school environment that supports student welfare. This activity aims to develop Eco-Canteen facilities to encourage healthier lifestyles, improve academic performance, and support the overall development of children in an educational environment through an Adaptive-Reuse approach to unused prayer room buildings. The process of designing the old prayer room building into a canteen involved structural evaluation, creating a healthy catteen design and a renovation process to create a safe, clean and environmentally friendly canteen for the entire school community. The methods used include drawing the existing floor plan, evaluating the condition of the old building, designing an eco-canteen and providing assistance. The assistance activities carried out include arranging green spaces, placing healthy living posters, and creating murals with environmental education messages in the canteen area. The design of this eco-canteen functions to support environmentally friendly behavior, support creativity and take steps towards sustainable education, so that with the existence of an eco-canteen at SMAN 1 Padalarang it is hoped that it can become a model for other schools in implementing the concept of a sustainable, healthy canteen.